Ursodeoxycholic acid protects interstitial Cajal-like cells in the gallbladder from undergoing apoptosis by inhibiting TNF-α expression - WAN Jiang-fan; CHU Shi-feng; ZHOU Xin; LI Yue-ting; HE Wen-bin; TAN Feng; LUO Piao; AI Qi-di; WANG Qi; CHEN Nai-hong (Acta Pharmacologica Sinica, 2018)
Hypomotility is a common symptom of gallstone disease, which is accompanied by a loss of interstitial Cajal-like cells (ICLCs) in the gallbladder. Ursodeoxycholic acid (UDCA) is widely used in treating gallstone disease, and has shown anti-apoptotic and anti-inﬂammatory effects apart from its ability to dissolve gallstones. In this study, we investigated the anti-apoptotic and anti-inﬂammatory effects of UDCA on ICLCs in guinea pigs with gallstones. Guinea pigs were fed a high-cholesterol diet for 8 weeks to induce the formation of gallstones. A group of animals was administered UDCA (50 mg·kg-1·d-1, ig) simultaneously. At the end of 8 weeks, the animals were euthanized with anesthesia, cholecystectomy was performed immediately and gallbladder was collected for further analysis. We showed that in the model group the contractility of gallbladder muscle strips in response to both acetylcholine (ACh) and CCK-8 was severely impaired, which was significantly improved by UDCA administration. Furthermore, UDCA administration significantly reduced the apoptotic ratio of ICLCs, based on the observation of co-localization imaging of apoptotic cells and c-kit-positive cells. Western blotting analysis and real-time PCR results revealed that the TNF-α/Caspase8/Caspase3 pathway was suppressed in the UDCA-treated animals, confirming the anti-apoptotic effect of UDCA in the gallbladder. The H&E staining showed that UDCA administration significantly attenuated inﬂammatory cell infiltration in the gallbladder wall. In conclusion, UDCA can protect ICLCs in the gallbladder from undergoing apoptosis by inhibiting the TNF-α/Caspase8/caspase3 pathway.